1976
DOI: 10.1007/bf01869147
|View full text |Cite
|
Sign up to set email alerts
|

Effect of transepithelial concentration gradients on the passive fluxes of sodium across toad bladder

Abstract: Bidirectional sodium fluxes across toad bladder were measured after eliminating active transport with ouabain. Mucosal sodium concentration, Cm, was progressively reduced (from 114 to 3 mM) while serosal sodium remained constant. Potential difference was maintained at zero by current passage. The ratio, Q, of the bulk permeability coefficient for sodium, P, to the tracer sodium permeability coefficient, P, was found to remain constant as Cm decreased. Equations were derived on this basis for bidirectional flux… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
1

Year Published

1977
1977
1980
1980

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(23 citation statements)
references
References 7 publications
0
22
1
Order By: Relevance
“…In recent studies of electrolyte permeation of toad bladder, we have observed that the effects of gradients of electrical potential [4-], concentration [5], or both [6] on unidirectional and net fluxes of ions conform closely to the predictions of a model based on a constant ratio of bulk permeability coefficient to tracer permeability coefficient. This ratio is the same as the ratio of bulk diffusion coefficient to '~ tradiffusion coefficient", as defined by Albright and Mills [1-].…”
mentioning
confidence: 52%
See 4 more Smart Citations
“…In recent studies of electrolyte permeation of toad bladder, we have observed that the effects of gradients of electrical potential [4-], concentration [5], or both [6] on unidirectional and net fluxes of ions conform closely to the predictions of a model based on a constant ratio of bulk permeability coefficient to tracer permeability coefficient. This ratio is the same as the ratio of bulk diffusion coefficient to '~ tradiffusion coefficient", as defined by Albright and Mills [1-].…”
mentioning
confidence: 52%
“…Bladder sacs of Dominican toads (Bufo marinus) were prepared and mounted as previously described [4][5][6].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations